A new approach in the one-step synthesis of α-MnO2via a modified solution combustion procedure. Issue 18 (24th August 2022) - Moqaddam, Mahsa Mohammadi; Mirjalili, Mostafa; Khaki, Jalil Vahdati; Beidokhti, Sahar Mollazadeh
Abstract : Synthesis of α-MnO2 nano powders via a modified one-step solution combustion method. Particle size and morphology are investigated to determine how the initial composition and adiabatic temperature of the synthesis affect the phase evolution and properties of the product. Abstract : Manganese oxides were synthesized systematically via the solution combustion procedure using two kinds of fuels, namely glycine and urea. The influences of the type of fuel and the fuel ratio were deeply investigated to explain the phase evolution and morphology of the product. The synthesized nanostructured powder was characterized by X-ray diffraction, particle size analysis, and FESEM. Furthermore, the thermodynamic aspects of all the synthesis reactions were studied by the calculation of the adiabatic temperature. Various manganese oxides, such as MnO, Mn3 O4, Mn2 O3, and MnO2, were obtained by varying the fuel ratio from 0.15 to 2. It was found that decreasing the fuel ratio promoted the formation of MnO2 by declining the combustion temperature and reductive conditions of the system. However, α-MnO2 could be simply achieved by adding KNO3 in a modified solution combustion process under fuel-lean conditions. Further heat treatment of the product was found to increase the crystallinity of the α-MnO2 nanoparticles.